2001
DOI: 10.1002/1097-4644(20010601)81:3<453::aid-jcb1059>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of 11?-hydroxysteroid dehydrogenase in rat osteoblastic cells: Pre-receptor regulation of glucocorticoid responses in bone

Abstract: 11 beta-hydroxysteroid dehydrogenase (11 beta-HSD) acts as a pre-receptor signaling mechanism for corticosteroids by regulating the access of active glucocorticoids to both glucocorticoid (GR) and mineralocorticoid receptors (MR). To examine the relationship between endogenous glucocorticoid metabolism and osteoblast function, we have characterized the expression of 11 beta-HSD isozymes in rat osteosarcoma cells. Analysis of mRNA from ROS 25/1, UMR 106 and ROS 17/2.8 cells revealed transcripts for both 11 beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 49 publications
(46 reference statements)
2
13
3
Order By: Relevance
“…The 11b-HSD1 enzyme metabolises endogenous glucocorticoids, cortisone and cortisol, in a bidirectional manner, whereas 11b-HSD2 is a unidirectional inactivator of endogenous glucocorticoids. We have previously demonstrated that OS cell lines express the 11b-HSD2 enzyme (Bland et al 1999, Eyre et al 2001. This is in contrast to normal osteoblasts that express the 11b-HSD1 enzyme (Cooper et al 2000.…”
Section: Introductioncontrasting
confidence: 85%
“…The 11b-HSD1 enzyme metabolises endogenous glucocorticoids, cortisone and cortisol, in a bidirectional manner, whereas 11b-HSD2 is a unidirectional inactivator of endogenous glucocorticoids. We have previously demonstrated that OS cell lines express the 11b-HSD2 enzyme (Bland et al 1999, Eyre et al 2001. This is in contrast to normal osteoblasts that express the 11b-HSD1 enzyme (Cooper et al 2000.…”
Section: Introductioncontrasting
confidence: 85%
“…However, our results did not reveal any clear skeletal phenotype of HSD1 Ϫ/Ϫ mice. Previous in vitro data have demonstrated that osteoblastic overexpression of 11␤HSD1 led to decreased cell proliferation and in- creased cell differentiation (20). However, in our experiments 11␤HSD1 Ϫ/Ϫ bone cells did not reveal any change in their proliferation or expression of osteoblastic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mice with targeted GR gene disruption exhibit bone marrow disfunctions [33], suggesting that glucocorticoids play a vital role in both fetal bone and thymus development. Although 11␤-HSD1 activity has been reported in both adult and fetal human bone [38] and 11␤-HSD2 mRNA has been detected in rat osteoblastic cells [39], neither isoform was expressed in the skeleton of the embryonic mice utilized in the current study. It is likely therefore that GR as well as 11␤-HSD1 and/or 11␤-HSD2 may be switched on in the mouse bone and thymus postnatally.…”
Section: Discussionmentioning
confidence: 99%